EVALUATING THE IMPACT OF AI–POWERED TUTORS MATHGPT AND FLEXI 2.0 IN ENHANCING CALCULUS LEARNING - Alvarez, Joel I. (LPPM Universitas Jambi, 2024)
This study evaluates the effectiveness of AI-driven technologies, Flexi 2.0 and MathGPT, in enhancing personalized learning and advanced cognitive abilities among pre-service mathematics educators participating in Calculus I. Participants were allocated to a control group receiving conventional training and an experimental group utilizing AI technology, applying a quantitative experimental design. Data were gathered utilizing validated evaluations, surveys, and interviews. The results indicated that students employing AI tutors showed significant improvements in problem-solving and personalized learning compared to the control group. Concerns arose regarding potential over-reliance on AI, underscoring the need for rigorous criteria to guarantee that students engage actively in learning rather than passively receiving AI-generated responses. The findings suggest that educators should create activities requiring students to critically evaluate AI-generated responses to promote independent thinking. The findings highlight the potential of AI in mathematics education while stressing the importance of ethical considerations and teacher oversight. It requires both students and staff training to adapt to improvements in AI inside education. The study reveals that while AI can improve learning outcomes, careful implementation is essential for its effective and responsible use in educational settings.